Improvement of ASL basd MR angiography for novel applications - Özyurt, Onur. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2017., 2017)
In this study, a custom four dimensional arterial spin labeling angiography (4D ASL) sequence and a proof-of-concept software tool to integrate 4D ASL data to routine scanning were implemented. One of the aims of this study was to test whether the combined use of 4D ASL and contrast-enhanced MR angiography (4D CE-MRA) can work as a prospective alternative to digital subtraction angiography (DSA) for the delineation of the AVM nidus in stereotactic radiosurgery (SRS) planning. Our results indicate that high reproducibility and agreement with experts are achievable without using DSA. The combined use of high temporal resolution 4D ASL and high spatial resolution and vessel-to-background contrast 4D CE-MRA provided su cient spatiotemporal angiographic information for the delineation of AVM niduses. Another application of 4D ASL is the testing of arterial input models which are used for blood ow quanti cation in ASL perfusion studies. The accuracy of quanti ed parameters (blood ow, arterial transit times etc.) is signi cantly e ected by the model choice. For this purpose, we have derived analytical solutions of a more realistic model describing the time evolution of the labeled blood. The e ects of varying arterial input parameters on the theoretical ASL signal have been investigated|Keywords : arterial spin labeling, ASL, contrast-enhanced MR angiography, stereotactic radiosurgery planning, ASL dispersion models.
Keywords: Dispersion.; Radiosurgery.